2021
DOI: 10.21203/rs.3.rs-400598/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of CDC20 As an Immune Infiltration-Correlated Prognostic Biomarker in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is a malignancy with a poor prognosis. Some E3 ubiquitin-protein ligases play essential roles in HCC development. We aimed to explore a hub E3 ubiquitin-protein ligase gene and verify its association with prognosis and immune cell infiltration in HCC. We identified cell division cycle 20 (CDC20) as a hub E3 ubiquitin-protein ligase in HCC by determining the intersecting genes in a protein-protein interaction (PPI) network of differentially expressed genes (DEGs) in HCC data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Cell division cycle 20 (CDC20) was identified associated with TILs, including CD8 + T cells, monocytes, and exhausted T cells in hepatocellular carcinoma (HCC). 45 Additionally, DNA topoisomerase II alpha (TOP2A), AURKA, cell division cycle-associated 5 (CDCA5), Xenopus kinesin-like protein 2 (TPX2), centromere protein F (CENPF), and DNA replication factor 1 (CDT1) can be used as independent prognostic factors and were positively associated B cells, CD4 + T cells, macrophages and dendritic cells in HCC, respectively. [46][47][48] In our study, we also found differential CCGs expression, together with immune infiltration levels in CD4 T activated memory cells, CD8 T central cells, correlated with BLCA prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell division cycle 20 (CDC20) was identified associated with TILs, including CD8 + T cells, monocytes, and exhausted T cells in hepatocellular carcinoma (HCC). 45 Additionally, DNA topoisomerase II alpha (TOP2A), AURKA, cell division cycle-associated 5 (CDCA5), Xenopus kinesin-like protein 2 (TPX2), centromere protein F (CENPF), and DNA replication factor 1 (CDT1) can be used as independent prognostic factors and were positively associated B cells, CD4 + T cells, macrophages and dendritic cells in HCC, respectively. [46][47][48] In our study, we also found differential CCGs expression, together with immune infiltration levels in CD4 T activated memory cells, CD8 T central cells, correlated with BLCA prognosis.…”
Section: Discussionmentioning
confidence: 99%